1979
DOI: 10.1111/j.1939-0025.1979.tb02585.x
|View full text |Cite
|
Sign up to set email alerts
|

Some evidence of race bias in the diagnosis and treatment of the juvenile offender.

Abstract: Clinical and epidemiological evidence is presented indicating that many more black delinquent children and their families fail to receive needed psychiatric and medical services than do white delinquents. Explanations and implications of the reluctance or inability of white mental health professionals to diagnose serious psychopathology in the black delinquent population are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 8 publications
(2 reference statements)
1
44
0
Order By: Relevance
“…For example, data have shown that symptoms that would have been recognized as pathological in White juvenile offenders were either ignored or incorrectly assessed in Black juveniles by predominantly White mental health professionals (Lewis et al, 1979). Such disparities are attributed to ethnocentrism among White professionals whose clinical standards for assessment exclude "the social reality of Blackness" (Martin & Grubb, 1990, p. 264).…”
Section: Theoretical Expectationsmentioning
confidence: 98%
“…For example, data have shown that symptoms that would have been recognized as pathological in White juvenile offenders were either ignored or incorrectly assessed in Black juveniles by predominantly White mental health professionals (Lewis et al, 1979). Such disparities are attributed to ethnocentrism among White professionals whose clinical standards for assessment exclude "the social reality of Blackness" (Martin & Grubb, 1990, p. 264).…”
Section: Theoretical Expectationsmentioning
confidence: 98%
“…Woolf (1988) lists several factors that impede provision of adequate health services to this population: 1) the assumption that teenagers are usually healthy, 2) other specialists For (i.e., someone else) will provide the medical care, 3) the subtle effects of institutional racism (i.e., white teens receive more services than black teens), and 4) care providers may hold a bias that delinquents are unattractive, difficult and unpleasant. Others concur with this assessment (see e.g., Lewis, Balla & Shanck, 1979;Farrow, 1984). Providers caring for these groups soon realize they are different from &dquo;normal&dquo; adolescents.…”
Section: Introductionmentioning
confidence: 80%
“…Regardless of cause and effect questions, there is no doubt that many delinquents suffer from school failure (Owens, 1985;Lewis et al, 1979;Farrow, 1984;Phillip & Philip, 1984;Burgess et al, 1987;Cavaiola & Schiff, 1988;Hanson et al, 1984;Lewis, Moy, et al, 1984;Lewis, Pincus, et al, 1988;Loeber & Dishion, 1983;Oats, 1984;Papemy & Deisher, 1983;Imperio & Chabot, 1988;Tolan, 1988;Walsh & Beyer, 1987;Grande, 1988;Lane, 1980;Leyser & Abrams, 1982;McKay & Brumback, 1980;Meltzer, Roditi, & Fenton, 1986;Nylander, 1981;Schuster & Guggenheim, 1982).…”
Section: Poor Educational Masterymentioning
confidence: 96%
See 1 more Smart Citation
“…Secondly it is reported that mental illness goes unrecognised in most black offenders whose behaviour is labelled as 'bad'; this would explain the higher contact with criminal justice agencies. Black people being perceived as more threatening may account for some degree of rnisdiagnosis (Bolton, 1984) but difficulties of conmunication and a failure of interventions/aftercare when illness is not recognised is also instrumental (Pasamanick, 1963;Lewis et at. 1979;Dolan et at.…”
Section: Introductionmentioning
confidence: 98%